Clinical application of urethral catheter in reconstruction of arteriovenous fistula vessel obstruction - SUN Xi-feng; GENG Xin-jie; GAO Hui; WANG Shu-xiang; XU Da-yu (Linchuang shenzangbing zazhi)
Objective To explore the advantages and disadvantages of surgical operation combined with urethral catheter thrombectomy and dilation for the treatment of arteriovenous fistula failure, and to provide new ideas for the treatment of long-term hemodialysis patients with fistula vessel obstruction due to thrombosis caused by internal fistula vessel stenosis. Methods Thirty-six patients with complications of arteriovenous fistula in the forearm caused by thrombosis were enrolled in the study. The arterialized cephalic vein was incised above the arteriovenous anastomosis, and the urethral catheter was used to remove the thrombus and expand the proximal stenosis. At last,vascularanastomosis and incision closure were performed. The clinical success rate was observed, and the internal diameter of the internal fistula vessel was measured with ultrasonic measurement before and after the operation. The postoperative vascular patency rate was calculated and the postoperative complications were observed. The observation lasted a total of 12 months. Results All the 34 patients had significant tremors after operation. The internal fistula construction was used for hemodialysis on the second day after operation. The dialysis flow rate was above 200 mL/min. The clinical success rate was 94.4%. The average internal diameter of the vascular stenosis site was(3.1±0.6) before operation(4.5±0.8) after operation, with the difference of statistical significance(P<0.05,The stenosis after treatment was significantly improved. K-M curve analysis showed a patency of 80%. No severe postoperative complications occurred in 36 patients. Only 2 cases of swollen hand syndrome occurred and the symptoms disappeared after treatment. Conclusions Surgical operation combined with urethral catheter thrombectomy + dilatation is suitable for patients with partial arteriovenous fistula obstruction. In particular, for primary medical institutions that cannot carry out PTA and other techniques,it has special advantages and has certain application prospects.